Optimizing Customer Retention in Modern Retail: The Role of Customer Experience and Relationship Quality - Suriansha, Reza; Diposumarto, Ngadino Surip; Muharam, Hari (The Eastasouth Journal of Social Science and Humanities, 2024)
The customer's position is the spearhead of business, including modern retail, for this reason, this research aims to find ways to optimize customer retention in modern retail with the role of relationship quality, and customer experience in Ramayana department stores. The population in this study were customers of Ramayana department stores in the DKI Jakarta area. The sampling technique used proportional random sampling with a sample size of 400 customers of Ramayana department stores. The data analysis method used in this research is path analysis using JASP software. This research produces conclusions 1). Relationship quality is proven to have a positive and significant influence on Customer Experience at Ramayana Department Store. 2) Customer Experience is proven to have a positive and significant influence on Customer Retention at Ramayana Department Store. 3) Relationship quality has a positive effect on Customer Retention through Customer Experience as full mediation at Ramayana Department Store.